Making the Most of Biostratigraphic Data; Examples from Early Cretaceous to Late Jurassic Shallow Marine Sand Units in Papua New Guinea and Australasia - Mike Bidgood; Monika Dlubak; Mike Simmons (Ikatan Ahli Geologi Indonesia, 2015)
A fundamental task in the exploration workflow is the mapping of reservoir sand units within a broader paleogeography. Such maps help, for example, to predict reservoir extent and link sands back to likely sediments sources thereby helping to improve reservoir quality predictions. If these sand units are multiple bodies within a relatively narrow time-stratigraphic interval, mapping of individual sands can be difficult if we rely on simple lithostratigraphic differentiation, or chronostratigraphic terminology (“ages”) for correlation.An example of this is shown from the Early Cretaceous to Late Jurassic shallow marine sands of southeast Papua New Guinea and Australasia. Previously correlated only on a broad timescale and often with overlapping age-range for individual lithostratigraphic units, it can be difficult to determine the precise stratigraphic position of each of these sands (e.g. the important Toro Sandstone reservoir) which in turn can affect interpretations regarding their exploration and production characteristics.The evaluation of large, public-domain, biostratigraphic datasets has allowed for the construction of a detailed “synthesis biozonation” for the area which permits more reliable identification and stratigraphic placement of individual sand units and which further allows for improved correlation at local and regional scale and improved mapping.